G50(P) A single centre paediatric gastroenterology unit experience of use of peristeen, trans-anal irrigation system for paediatric faecal incontinence. (27th April 2016) - Sharma, V; Gordon, K; Stevens, S; Mew, N; Rodrigues, A; Howarth, L
Abstract : Aim: To evaluate the efficacy and safety of Peristeen for the rescue treatment of faecal incontinence in children with chronic idiopathic constipation who have not responded to long term laxative management. Methods: This study reports the results of a pilot to trial Peristeen in children with severe treatment non-responsive idiopathic constipation. Prospective data was collected on children who were still regularly soiling despite intensive input and laxative advice from the nurse-led constipation service. Children who started Peristeen treatment between January 2014 to December 2014 were reviewed. All children with faecal incontinence due to idiopathic chronic constipation who began Peristeen trans-anal irrigation at home were included for data analysis. Children referred with neurological and surgical causes of constipation were excluded. Results: 11 children, 8 boys and 3 girls, with idiopathic chronic constipation and soiling were included in the study. Two children, one with autistic spectrum disorder and another with ADHD, did not tolerate Peristeen and treatment was withdrawn. Mean age was 12.2 years. Duration of constipation was noted to be: 2–5 years in one child, 5–10 years in 8 children and more than 10 years in 2 children. Soiling was noted for 1 year in one child and more than 5 years in 10 children. 63% (7) of children showed improvement in soiling and 45% (5) in chronic constipation on Peristeen treatment. Peristeen was successfully stopped in one child and in another weaned from once daily to twice in a week regimen. Social activity data showed poor school attendance (<85%) in 5 children which significantly improved in 3 children. Out of 3 children with severe impact on their social functioning, one child reported significant improvement in anxiety and self-confidence. His academic performance and relationship with his peers significantly improved. No adverse complications reported. Conclusion: In this small pilot study Peristeen appears to be a safe and effective treatment for children with intractable idiopathic constipation and faecal incontinence not resolving with long term specialist constipation and laxative management. In children without significant behavioural problems Peristeen appears to be well tolerated. There appears to be improvement in social activity and school attendance in children on Peristeen treatment.